2020
DOI: 10.3168/jds.2019-16966
|View full text |Cite
|
Sign up to set email alerts
|

Can greenhouse gases in breath be used to genetically improve feed efficiency of dairy cows?

Abstract: There is considerable interest in improving feed utilization of dairy cattle while limiting losses to the environment (i.e., greenhouse gases, GHG). To breed for feed-efficient or climate-friendly cattle, it is first necessary to obtain accurate estimates of genetic parameters and correlations of feed intake, greenhouse gases, and production traits. Reducing dry matter take (DMI) requirements while maintaining production has high economic value to farmers, but DMI is costly to record and thus limited to small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
2
26
2
Order By: Relevance
“…Genetic correlations were positive and moderate between MeP and MY (0.29), and between MeP and ECM (0.45), the first was similar to the correlation reported (0.26) by Breider et al (2018) in Australian Holstein whereas the latter was similar to the correlation reported (0.43) by Lassen and Løvendahl (2016) in Danish Holstein. Likewise, Difford et al (2020) reported genetic correlation of 0.35 between CH 4 concentration and FPCM in a combined data set with Danish and Dutch Holstein cows. Furthermore, genetic correlations between GSMet and MY (0.41) and ECM (0.59) were higher than with MeP.…”
Section: Correlations Between Methane Traits and Production Traitsmentioning
confidence: 90%
See 3 more Smart Citations
“…Genetic correlations were positive and moderate between MeP and MY (0.29), and between MeP and ECM (0.45), the first was similar to the correlation reported (0.26) by Breider et al (2018) in Australian Holstein whereas the latter was similar to the correlation reported (0.43) by Lassen and Løvendahl (2016) in Danish Holstein. Likewise, Difford et al (2020) reported genetic correlation of 0.35 between CH 4 concentration and FPCM in a combined data set with Danish and Dutch Holstein cows. Furthermore, genetic correlations between GSMet and MY (0.41) and ECM (0.59) were higher than with MeP.…”
Section: Correlations Between Methane Traits and Production Traitsmentioning
confidence: 90%
“…Furthermore, CH 4 data (from research and commercial herds) were filtered to only include weekly averages where a maximum of 3 d were missing within each week of measurement and each cow had a minimum of 3 weekly measurements. The concordance correlation coefficient between respiration chamber CH 4 emissions and sniffers (Guardian) CH 4 concentration is 0.77 (Difford et al, 2020). Both methodologies were described and compared previously (Difford et al, 2016).…”
Section: Data Collection: Methanementioning
confidence: 99%
See 2 more Smart Citations
“…Today, however, increased demand for food, forces breeders to raise high producing livestock breeds which convert animal feed into meat, milk and eggs (Pirlo and Car e 2013). Furthermore, these high producing breeds are very often held responsible of GHG emissions, even if several studies demonstrated the possibility for using GHG traits as large-scale indicator traits for genetically improving the accuracy of feed efficiency such as in dairy cows (Difford et al 2020), in beef cattle (Barwick et al 2019), in pigs (Alfonso 2019), and in poultry (Willems et al 2013). This may lead to the negligence of local breeds adapted in developing countries (Mathias and Mundy 2005).…”
Section: Measures Adopted By Breeders To Face Climate Changementioning
confidence: 99%